Statistical Study Regarding the Presence of Gram Bacteria in Patients with Cardiovascular Disease and Periodontal Disease - Ioana VOINESCU; Dumitru FERECHIDE (Modern Medicine)
Pathogenic bacteria, originating in the inflamed periodontium, can make their way into the body through the vascular system, either by entering the bloodstream or lymph directly or as internalized particles of immune cells. This research aims to investigate the existence of a potential connection between two pathologies – periodontitis and ischemic heart disease – by utilizing a DNA-DNA hybridization technique to highlight the presence of seven periodontal pathogens: A. actinomycetemcomitans, P. gingivalis, P. endodontalis, P. intermedia, T. forsythia, C. rectus and F. Nucleatum. The study was conducted over a period of 3 years on a sample consisting of 119 patients with cardiovascular disease and periodontal disease, divided into 3 groups by pathologies, as follows: the first group consisted of 31 patients with ischemic cardiomyopathy, the second group consisted of 43 patients with periodontal disease and ischemic cardiomyopathy, and the third group consisted of 45 patients with periodontal disease. The results show the possibility of a correlation between the composition of the bacterial flora in the group of patients with cardiac disease and those with associated pathologies. In conclusion, we may state that periodontitis may be seen as a risk factor in heart disease, which may certify the possibility of an etiological connection between the two pathologies.